Sulfate reduction and sulfide oxidation in extremely steep salinity gradients formed by freshwater springs emerging into the Dead Sea. Issue 3 (8th December 2014) - Häusler, Stefan; Weber, Miriam; Siebert, Christian; Holtappels, Moritz; Noriega-Ortega, Beatriz E.; De Beer, Dirk; Ionescu, Danny
Abstract: Abundant microbial mats, recently discovered in underwater freshwater springs in the hypersaline Dead Sea, are mostly dominated by sulfur-oxidizing bacteria. We investigated the source of sulfide and the activity of these communities. Isotopic analysis of sulfide and sulfate in the spring water showed a fractionation of 39–50‰ indicative of active sulfate reduction. Sulfate reduction rates (SRR) in the spring sediment (< 2.8 nmol cm −3 day −1 ) are too low to account for the measured sulfide flux. Thus, sulfide from the springs, locally reduced salinity and O2 from the Dead Sea water are responsible for the abundant microbial biomass around the springs. The springs flow is highly variable and accordingly the local salinities. We speculate that the development of microbial mats dominated by either Sulfurimonas/Sulfurovum-like or Thiobacillus /Acidithiobacillus-like sulfide-oxidizing bacteria, results from different mean salinities in the microenvironment of the mats. SRR of up to 10 nmol cm −3 day −1 detected in the Dead Sea sediment are surprisingly higher than in the less saline springs. While this shows the presence of an extremely halophilic sulfate-reducing bacteria community in the Dead Sea sediments, it also suggests that extensive salinity fluctuations limit these communities in the springs due to increased energetic demands for osmoregulation. Abstract : Sulfur oxidizers and reducers are active around underwater freshwater springs in the Dead Sea. They benefit from compounds provided by the springs but are inhibited by fluctuations in water flow. Abstract :